CDK Inhibitors Induce Mitochondria-mediated Apoptosis Through the Activation of Polyamine Catabolic Pathway in LNCaP, DU145 and PC3 Prostate Cancer Cells - Çoker Gürkan, Ajda; Calcabrini, Annarica; Agostinelli, Enzo; Palavan Unsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Bentham Science Publ Ltd, Executive Ste Y-2, Po Box 7917, Saif Zone, 1200 Br Sharjah, U Arab Emirates, 2014)
Androgen signaling is critical in prostate cancer development and progression. The co-existence of hormone responsive and irresponsive cells due to functional androgen receptor (AR) in prostate gland is the major obstacle in prostate cancer therapy models. Targeting aberrant cell cycle by novel cell cycle blocking agents is a promising strategy to treat various types of malignancies. Purvalanol and roscovitine are cyclin dependent kinase (CDK) inhibitors able to activate apoptotic cell death by inducing cell cycle arrest at G1/S and G2/M phases in cancer cells. Polyamines are unique cationic amine derivatives involved in the regulation of cell proliferation. Although the elevated intracellular level of polyamines (putrescine, spermidine and spermine) is typical for prostate gland, abnormal regulation of polyamine metabolism might result in rapid cell proliferation and, thus in prostate cancer progression. Therefore, treatment with drug-induced depletion of intracellular polyamine levels through the activated polyamine catabolism is critical to achieve successful strategies for prostate cancer. In this study we aimed to investigate the apoptotic efficiency of CDK inhibitors in three prostate cancer cell lines (LNCaP, DU145 and PC3), showing different AR expression profile. We found that both purvalanol and roscovitine were able to induce apoptosis at moderate cytotoxic concentrations by decreasing mitochondria membrane potential. The apoptotic effect of both CDK inhibitors was due to activation of caspases by modulating Bcl-2 family members. The efficiency of drugs was quite similar on the three prostate cell lines used in this study. However, DU145 cells were found the least sensitive against CDK inhibitors while purvalanol was more potent than roscovitine. Similarly to classical chemotherapeutic agents, both drugs could up-regulate polyamine catabolic enzymes (SSAT, SMO and PAO) in cell type dependent manner. Transient silencing of SSAT and/or inhibition of PAO/SMO with MDL72527 prevented CDK inhibitors-induced apoptotic cell death in DU145 and PC3 cells. Although roscovitine was less effective in DU145 cells, pre-treatment with alpha-difluoromethylornithine (DFMO), an inhibitor of ODC, enhanced the roscovitine-induced apoptotic cell death through the cleavage of caspase-9 and caspase-3. Therefore, we conclude that polyamine catabolism might have essential role in the cellular responses against CDK inhibitors in different androgen-responsive or irresponsive prostate cancer cells.
Keywords: Polyamines; CDK inhibitors; purvalanol; roscovitine; prostate cancer; Cyclin-Dependent Kinase; Spermine Oxidase; Ornithine-Decarboxylase; Androgen Receptor; Epithelial-Cells; Down-Regulation; Leukemia-Cells; R-Roscovitine; Amine Oxidase; Purvalanol-A